2019
DOI: 10.1021/acs.jmedchem.9b00687
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Zanubrutinib (BGB-3111), a Novel, Potent, and Selective Covalent Inhibitor of Bruton’s Tyrosine Kinase

Abstract: Aberrant activation of Bruton’s tyrosine kinase (BTK) plays an important role in pathogenesis of B-cell lymphomas, suggesting that inhibition of BTK is useful in the treatment of hematological malignancies. The discovery of a more selective on-target covalent BTK inhibitor is of high value. Herein, we disclose the discovery and preclinical characterization of a potent, selective, and irreversible BTK inhibitor as our clinical candidate by using in vitro potency, selectivity, pharmacokinetics (PK), and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
273
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(280 citation statements)
references
References 41 publications
(64 reference statements)
6
273
0
1
Order By: Relevance
“…However, zanubrutinib is more selective than ibrutinib against off-target kinases, including epidermal growth factor receptor, Janus tyrosine kinase 3, human epidermal growth factor receptor 2, Tec protein-tyrosine kinase, and inducible tyrosine kinase. 6 The increased selectivity of zanubrutinib for BTK may result in a lower incidence and severity of off-target toxicities linked to inhibition of the aforementioned kinases. Emerging clinical data have shown that zanubrutinib as a single agent and in combination with other therapies resulted in high rates of objective response in patients with B-cell malignancies, including Waldenström's macroglobulinemia, MCL, and chronic lymphocytic leukemia, 7-9 consistent with its near-complete BTK occupancy and target engagement in target tissues (median occupancy of 100% in lymph nodes).…”
Section: How Might This Change Clinical Pharmacol-ogy or Translationamentioning
confidence: 99%
“…However, zanubrutinib is more selective than ibrutinib against off-target kinases, including epidermal growth factor receptor, Janus tyrosine kinase 3, human epidermal growth factor receptor 2, Tec protein-tyrosine kinase, and inducible tyrosine kinase. 6 The increased selectivity of zanubrutinib for BTK may result in a lower incidence and severity of off-target toxicities linked to inhibition of the aforementioned kinases. Emerging clinical data have shown that zanubrutinib as a single agent and in combination with other therapies resulted in high rates of objective response in patients with B-cell malignancies, including Waldenström's macroglobulinemia, MCL, and chronic lymphocytic leukemia, 7-9 consistent with its near-complete BTK occupancy and target engagement in target tissues (median occupancy of 100% in lymph nodes).…”
Section: How Might This Change Clinical Pharmacol-ogy or Translationamentioning
confidence: 99%
“…4 Zanubrutinib (BGB-3111) is a highly specific second-generation BTKi, with favorable oral bioavailability seen in preclinical studies. 5,6 Compared with ibrutinib, zanubrutinib has shown greater selectivity for BTK with fewer off-target effects based on multiple in vitro enzymatic and cell-based assays (see supplemental Table 1 in Tam et al 7 ). In a recent head-to-head phase 3 comparison in Waldenström macroglobulinemia (WM), zanubrutinib treatment was associated with less toxicity, particularly cardiovascular toxicity, and a trend toward better response quality.…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant activation of Bruton tyrosine kinase has a key role in the tumorigenesis of B-cell lymphoma ( Guo et al 2019 ). Its abrogation seems to protect lungs from acute immune-induced or lethal influenza-induced injuries ( Florence et al 2018 ; Krupa et al 2014 ) as well as sepsis-induced injury ( Zhou et al 2014 ).…”
Section: Potential Anticancer Drugs For Covid-19mentioning
confidence: 99%